Quality of life of patients with knee osteoarthritis - Shrestha, Rajani (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Osteoarthritis (OA) is a non-inflammatory degenerative disorder of the joint. It has negative impact on health related quality of life (QOL), both in physical and mental health. This study aimed to assess QOL of patient with knee osteoarthritis.Methods: A descriptive cross-sectional study was conducted in outpatient department of orthopedic in Patan hospital, Patan Academy of Health Sciences. Non-probability purposive sampling technique was used. Data was collected from 21st July to 18th August 2017 among 125 knee osteoarthritis patients by face-to-face interview using structured interview.Results: Overall QOL of patients with knee osteoarthritis was good in mental health component mean score (62.09) and poor in physical health with a mean score of (38.18). The physical component of QOL was significantly associated with age (p